Education on Feed Provision Through Fermentation Technology in Galang Kangin Goat Farmers Group: English - SANJAYA, I GUSTI AGUS MAHA PUTRA; Kaca, I.N.; Devani, I.M.P.H.; Suryawan, I.G.B.; Krismayana, I.P. (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Goat feed fermentation aims to increase nutritional value, extend shelf life, and make feed easier for livestock to digest. The objective of this activity is to improve partners' knowledge in managing their livestock businesses based on the concept of green economy, and their skills in applying fermentation technology to forage and agricultural waste as high-nutrient feed for goats. The implementation methods of the community service activities included socialization, education, technology transfer, training, and mentoring. The results of these activities demonstrated an increase in knowledge and understanding among partner group members regarding the importance of applying green economy concepts to their livestock businesses. There was also an improvement in partners' knowledge and skills in processing forage and agricultural waste into high-nutrient livestock feed using feed fermentation techniques. The community service activities conducted at the Galang Kangin Goat Farming Group proceeded smoothly, with active participation from the activity partners. Based on the results of the pre-test and post-test administered, there was a 27% increase in knowledge and skills among the partner group members compared to previous levels.